EXAMINATION OF EMERGENCY LIGHTING SYSTEM FOR PASSENGER SHIPS AND FERRIES - Zalesińska, Małgorzata; Wandachowicz, Krzysztof (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2015)
Emergency lighting systems (system LLL) on passenger ships and ferries must even in the total smoke ensure proper conduct visual way to exit from the decks of ship. LLL systems must be installed in specific locations on ships and have proper photometric parameters after a specified time of their activation. The article presents the photometric requirements for LLL systems mounted on ships and passenger ferries, the results of laboratory tests and analysis of basic properties of typical materials used for photoluminescent strips and the procedure for testing the efficiency of light LLL system in real condition.